Conduct unbecoming fifteen military criminals, rogues and victims of justice from the Revolutionary War to Vietnam - Baron, Scott 1954-; Wise, James E. junior (McFarland & Company, Inc., Publishers, 2016)
"The authors examine such overlooked cases as the Somers Mutiny, the trial of the San Patricios and the Port Chicago Mutiny. These trials demonstrate that guaranteeing military justice...especially in the midst of armed conflict...is both a challenge and a necessity in a free society"...